Host stromal versican is essential for cancer-associated fibroblast function to inhibit cancer growth - Fanhchaksai K. (2017)
© 2015 UICC. The stroma provides a microenvironment that regulates tumor cell behavior. The extracellular matrix (ECM) has long been recognized to be important in tumor cell behavior, and previous studies have revealed the impact of individual matrix molecules on tumor progression. Although several reports have highlighted some central roles of tumor cell-expressed versican, the role of host stromal versican is not yet understood. In this study, we demonstrate that versican is an important molecule in the functional ECM structure and maintaining cancer-associated fibroblasts, using versican-negative QRsP11 fibrosarcoma cells. By their subcutaneous injection with cre-expressing adenoviruses to versican-floxed mice, we demonstrate that loss of host stromal versican facilitates tumor cell proliferation, and following angiogenesis, decreases cancer-associated fibroblasts, diminishes collagen fibers and alters hyaluronan distribution, concomitant with upregulation of hyaluronan, TGFβ and VEGF-mediated signaling. When the versican V3 variant consisting of G1 and G3 domains was expressed in tumor cells, it was integrated into the ECM, regained collagen fibers and cancer-associated fibroblasts and resulted in successful recovery of tumor growth inhibition, indicating that whatever cells produce, the G1 and G3 domains are adequate for versican function. Collectively, our results indicate a dynamic function of versican in the ECM that regulates tumor cell behavior. A greater understanding of the regulation of versican expression may contribute to the development of cancer therapies. What's new? The dynamic behavior of tumor cells is closely tied to the extracellular matrix (ECM) and changes in its composition and regulation that occur during tumorigenesis. In this study, loss of the stromal protein versican in mice was found to facilitate changes in the ECM that are conducive to tumor growth. Specifically, versican ablation led to declines in cancer-associated fibroblasts and collagen fibers and to changes in hyaluronan regulation. It also facilitated angiogenesis via elevated VEGF signaling. Further understanding of the factors that control versican expression could provide important insight for the development of novel therapeutic strategies.